The COVID‐19 outbreak in Italy: Initial implications for organ transplantation programs. Issue 7 (17th April 2020) - Angelico, Roberta; Trapani, Silvia; Manzia, Tommaso Maria; Lombardini, Letizia; Tisone, Giuseppe; Cardillo, Massimo
Abstract : The spread of Coronavirus Disease 2019 (COVID‐19) has already reached a pandemic dimension within a few weeks. Italy has been one of the first countries dealing with the outbreak of COVID‐19, and severe measures have been adopted to limit viral transmission. The spread of COVID‐19 may have several implications in organ transplant activity that physicians should be aware of. The initial experience gained during the COVID‐19 outbreak shows that around 10% of infected patients in Italy need intensive care management to overcome the acute respiratory distress syndrome. Due to the exponential rise of infected patients we are now facing an actual risk of saturation of intensive care unit (ICU) beds. A restriction in the number of ICU beds available for both donors and transplant recipients may unfavorably influence the overall donation activity, and eventually lead to a reduced number of transplants. Preliminary Italian data show that a 25% reduction of procured organs has already occurred during the first 4 weeks of COVID‐19 outbreak. This underlines the need to closely monitor what will be further happening in ICUs due to the COVID‐19 spread in the attempt to preserve transplant activity, especially in Western countries where deceased donors represent the major organ resource. Abstract : The initial experience gained during the coronavirus disease 2019 outbreak in Italy shows that the progressive saturation of the intensive care unit beds, due to the exponential rise of infected patients needing intensive care management, reduced the deceased donation activity by 25% within the first four weeks of spread, and may further unfavorably influence the solid organ transplantation activity without strong interventions in the healthcare system.